Fast and global reorganization of the chloroplast protein biogenesis network during heat acclimation. Issue 3 (27th December 2021) - Trösch, Raphael; Ries, Fabian; Westrich, Lisa Désirée; Gao, Yang; Herkt, Claudia; Hoppstädter, Julia; Heck-Roth, Johannes; Mustas, Matthieu; Scheuring, David; Choquet, Yves; Räschle, Markus; Zoschke, Reimo; et al.
Abstract: Photosynthesis is a central determinant of plant biomass production, but its homeostasis is increasingly challenged by heat. Little is known about the sensitive regulatory principles involved in heat acclimation that underly the biogenesis and repair of chloroplast-encoded core subunits of photosynthetic complexes. Employing time-resolved ribosome and transcript profiling together with selective ribosome proteomics, we systematically deciphered these processes in chloroplasts of Chlamydomonas reinhardtii. We revealed protein biosynthesis and altered translation elongation as central processes for heat acclimation and showed that these principles are conserved between the alga and the flowering plant Nicotiana tabacum . Short-term heat exposure resulted in specific translational repression of chlorophyll a -containing core antenna proteins of photosystems I and II. Furthermore, translocation of ribosome nascent chain complexes to thylakoid membranes was affected, as reflected by the increased accumulation of stromal cpSRP54-bound ribosomes. The successful recovery of synthesizing these proteins under prolonged acclimation of nonlethal heat conditions was associated with specific changes of the co-translational protein interaction network, including increased ribosome association of chlorophyll biogenesis enzymes and acclimation factors responsible for complex assembly. We hypothesize that co-translational cofactor binding and targeting might be bottlenecks under heat but become optimized upon heat acclimation to sustain correct co-translational protein complex assembly. Abstract : Heat exposure at 40°C leads to specific temporary changes of chloroplast translation, majorly affecting antenna proteins of the photosynthesis machinery.